Congenital protein C deficiency and superior sagittal sinus thrombosis causing isolated intracranial hypertension. Issue 5 (May 1994) - Confavreux, C; Brunet, P; Petiot, P; Berruyer, M; Trillet, M; Aimard, G
Abstract : The first case of a superior sagittal sinus thrombosis causing isolated intracranial hypertension as a result of congenital protein C deficiency is reported. Such a possibility must not be overlooked. Anticoagulation is recommended as a treatment for cerebral venous thrombosis. In the case of congenital protein C deficiency, vitamin K antagonists must be started cautiously due to the risk of skin necrosis.